Population limitation in birds - Newton, Ian, 1940- (Academic Press, 1998)
This book meets the demand for a comprehensive introduction to understanding the processes of population limitation. Recognized world-wide as a respected biologist and communicator, Dr. Ian Newton has now written a clear and detailed treatise on local scale population limiting factors in birds. It is based almost entirely on results from field studies, though it is set in a contemporary theoretical framework. The 16 chapters fall under three major section headings: Behavior and Density Regulation; Natural Limiting Factors; and Human Impacts. Population Limitation in Birds serves as a needed resource expanding on Dr. David Lacks research in this area of ornithology in the 1950s. It includes numerous line diagrams and beautiful illustrations by acclaimed wildlife artist Keith Brockie. Provides a sorely needed introduction to a long-established core subject in ornithology Focuses on local scale factors Written by a well-known biologist and effective communicator Includes numerous line diagrams and beautiful illustrations by acclaimed wildlife artist Keith Brockie.